Current update of first trimester preeclampsia screening in Asia. Issue 1 (15th October 2020) - Lin, Tzu‐Yi; Huang, Hui‐Yu; Chan, Kok‐Seong; Chen, Yen‐Tin; Chu, Fu‐Chieh; Shaw, Steven W.
Abstract: In consideration of high prevalence of preeclampsia, enormous studies attempted to look for strategies in early gestation. Hence, a powerful screening should be built up in first trimester. Then, Aspirin could be administrated for proper prevention. The objective of this article is reviewing the screening for preeclampsia in first trimester recently. To identify the high‐risk group precisely, an effective model should be recommended to Asian population. Articles related to first trimester screening of PE in Asia from databases of PubMed, ScienceDirect and Scopus were searched for this narrative review. The criteria included randomized clinical trials, observational prospective and retrospective cohort studies, case–control studies, systematic review and meta‐analysis and professional review articles. Screening models combining maternal factors, biophysical factors, ultrasound studies and biochemical factors achieved high predictive performance of preeclampsia. In Asia, the detection rate of the Fetal Medicine Foundation is superior to those of the American College of Obstetricians and Gynecologists and the National Institute for Health and Care Excellence . Consequently, this effective model from the Fetal Medicine Foundation should be continuously used for screening in first trimester for the Asian.